Association of infantile convulsions with paroxysmal dyskinesias (ICCA syndrome): confirmation of linkage to human chromosome 16p12-q12 in a Chinese family. - Lee, W; Tay, A; Ong, H; Goh, L; Monaco, A; Szepetowski, P (1998)
We have studied one family of Chinese origin, in which benign infantile convulsions and paroxysmal choreoathetosis (of the dystonic form) were co-inherited as a single autosomal dominant trait. This association is specific to ICCA syndrome, which we have recently described in four French families. Some patients in the new family also exhibit recurrence of epileptic seizures at a much later age, making the ICCA syndrome in this family atypical. DNA samples isolated from this family of 22 members (9 affected) have been tested with genetic markers at chromosome 16p12-q12, in which region the ICCA syndrome has previously been linked. Confirmation of linkage to this pericentromeric region of human chromosome 16 has been obtained and no critical meiotic recombination event has been detected in the ICCA region. This result suggests that, in contrast to marked clinical heterogeneity, the association of infantile convulsions with paroxysmal dyskinetic movements could be genetically homogeneous.